The Influence of the Deep Learning Approach on Students’ Problem-Solving Skills, Digital Literacy, and Learning Outcomes - Eviana Eviana; Halida Halida (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This research aims to analyze the influence of Deep Learning on problem-solving skills, digital literacy, and student learning outcomes. The background of this research is based on the educational needs of the 21st century, which require students' critical thinking skills, adequate digital literacy, and optimal academic achievement. This research was conducted quantitatively using a quasi-experimental method. The study involved 121 tenth-grade students, and the total sampling method was used to select the research sample. The research instruments consist of questionnaires on the Deep Learning approach to problem-solving skills, digital literacy, and learning outcomes tests. Data analysis using the MANOVA test to determine the partial and simultaneous influence of Deep Learning on the dependent variables. The research results show that Deep Learning has a significant effect on students' problem-solving skills, digital literacy, and learning outcomes, both partially and simultaneously. The results indicate that the application of Deep Learning can improve students' higher-order thinking skills and prepare them to face the challenges of the digital era. Therefore, to achieve sustainable improvement in learning processes and outcomes, teachers and educational institutions must integrate this approach into their teaching strategies.